Prevalence of congenital limb defects in Uttarakhand state in India - A hospital-based retrospective cross-sectional study - Sitanshu Barik; Naveen Pandita; Souvik Paul; Om Kumari; Vivek Singh (Elsevier, 2021)
Background: Congenital limb defects (CLD) occur when normal development of limbs is hampered during the intrauterine period. There is a paucity of literature regarding the prevalence and pattern of various congenital limb defects in India. The aim of this study is to assess the prevalence and pattern of various CLD using Swanson classification in the state of Uttarakhand, India. Methods: Retrospective study over a 6-year period was done. The prevalence of CLD was calculated by determining the live births from birth rate and total population from the 2011 census of the Government of India. Results: A total of 316 cases with a mean age of 3.2 ± 2.3 years (1 day-12 years) were included. Radial clubhand (n = 9, prevalence = 0.4 per 10,000 live births) was the most common CLD in upper limb. Idiopathic clubfoot (CTEV) (n = 158, prevalence = 7 per 10,000 live births) was the most common CLD in lower limb. Failure of formation (n = 12) was the most common defect in the lower limb whereas failure of differentiation (n = 16) was common in the upper limb. Discussion: This is the first study from any part of India depicting the prevalence of CLD, which can be used to formulate public health policies for early diagnosis and management of the same. Conclusion: The prevalence of CLD is 14 per 10,000 live births in Uttarakhand, India, which are comparable to various studies published from different parts of the world. Males are commonly involved with radial clubhand being common in the upper limb and CTEV being common in the lower limb.